ANALISIS KUALITAS PELAYANAN TOUR GUIDE DI DESTINASI WISATA BENTENG MARLBOROUGH BENGKULU - Heni Dwi Lestari; Novi Irawati; Herry Teguh Santoso (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Tourist satisfaction in a tourist destination can be created with an optimal service system and improving the quality of tourist destination attractiveness. In addition, it is also necessarygood skills that must be possessed by tour guides in carrying out their duties to provide good and correct information regarding tourist destinations or the surrounding area to be conveyed to tourists. This study aims to evaluate the quality of the Tour Guide in Fort Marlborough in Bengkulu city. The influence of the quality of the Tour Guide on the Fort Marlborough tourist destination in the city of Bengkulu has an impact on tourist satisfaction. The method used is a qualitative descriptive method which is carried out by means of in-depth interviews, participatory observation, documentary materials, and new methods through the study of materials on the internet. The analysis technique used is a fishbone diagram which is used in the process of identifying a problem and determining its cause. Based on the results of the research that has been carried out, it is found that the lack of Tour Guide is in accordance with the theory of Huang et (2015): professional competence, interpersonal skills and organization, empathy and problem solving. The advice given is that it is hoped that Tour Guides who join the MTG (Manada Tour Guide) must pay attention to the Tour Guide's knowledge of tourist objects and the skills of the Tour Guide. Developments that can be done include doing in-depth problem solving, as well as 5 other factors that must be owned by the Tour Guide to improve service quality performance, namely professionalism, competence, interpersonal skills and organization, empathy and problem solving.Keywords: Guide Effect; Tourist Satisfaction; Fort Marlborough Bengkulu